Sustainability Performance of the Retail Business and Supply Chain Collaboration-UK Perspective: A Literature Review - Islam Bhuyan, Abu Hasanat Md Monzurul; Afranie, Samuel Boafo; Habib, Md. Mamun (International Journal of Supply Chain Management, 2019)
The ever increasing pressure from the supply chain management stakeholders including governmental and non-governmental organization has indeed created the concerns for the firms to be more sustainable in their operational processes. The retail industry is considering potential solutions to enable them to be more sustainable and greener. This has called for a vertical collaboration within the supply chain stakeholders to promote the sustainable performance management. This research has analysed the article publications of years’ span period, which was from 2012 to 2018. To compare the research endeavours with the practices, this thesis also scrutinized the sustainable retail practices of top ten retail shop in the world. The findings of this research shows that supply chain collaboration and sustainable practices are correlated to the performance optimization efforts Keywords: Sustainability Performance, Risk Management, Transparency, Triple Bottom Line, and Supply Chain Collaboration